HDL & LDL Status in Untreated Newly Detected Type 2 Diabetic Patients (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
Objective: The study was conducted with a view to find out HDL & LDL status in newly detected untreated Type II diabetic patients. Methods: Study was carried out on 116 (66 male & 50 female) newly diagnosed untreated type 2 diabetes patients aged 40 - 65 years and were selected randomly for study. Fifty (25 male & 25 female) non diabetic subjects aged 40 - 65 years were randomly selected as control. Results: LDL - C was significantly higher (P